Penerapan Pembelajaran Berbasis Proyek Untuk Meningkatkan Kreativitas Peserta Didik Di Kelas IV Minu Hidayatul Mubtadiin - Nurul Hidayati; Fauzi Fadliansyah (Desanta Publisher, 2024)
This research aims to increase creativity through the STEAM-PjBL model on the subject of My Region and Natural Resources in class IV MINU Hidayatul Mubtadiin for the 2023/2024 academic year. Classroom action research (PTK) was carried out with two learning cycles. The data collection method consists of creativity test sheets for science learning. The results of the research showed that students in cycle I obtained an average score of 70.67%, or in the sufficient category, and the average score of student learning outcomes during cycle II increased to 91.52%, or in the very good category. . Therefore, an increase of 20.85% from qualifications based on cycle I to cycle II is sufficient to meet the good criteria. This research was stopped after cycle II because the success indicators had been reached and the qualifications for completion were reached. The conclusion of this research is that the STEAM-based project-based learning (PjBL) model can increase students' creativity on the subject of My Region and Natural Resources in class IV MINU Hidayatul Mubtadiin.